ANÁLISIS DE LAS APLICACIONES MÓVILES DE LAS TELEVISIONES GENERALISTAS ESPAÑOLAS Y PORTUGUESAS: INTERACTIVIDAD Y CONTENIDOS - Dr. José Juan VIDELA RODRÍGUEZ,Dra. María Josefa FORMOSO BARRO,Dr. Manuel GARCÍA TORRE (Fonseca, Journal of Communication, 2023)
This article makes an approach to the content and interactive options offered in mobile apps for tablets with Android and iOS operating systems by the Generalist Spanish and Portuguese television. This is an analysis through an ad hoc model that includes the different television channels included in the study: RTVE, ATRESMEDIA, MEDIASET, RTP, TVI and SIC. This analysis is highlighted the fact that Spanish television channels offer a wider range of content and more options of interaction between users and the media.